Activated Carbon Fiber Monoliths as Supercapacitor Electrodes - Gelines Moreno-Fernandez; Joaquin Ibañez; Jose M. Rojo; Mirko Kunowsky (Advances in Materials Science and Engineering)
Activated carbon fibers (ACF) are interesting candidates for electrodes in electrochemical energy storage devices; however, one major drawback for practical application is their low density. In the present work, monoliths were synthesized from two different ACFs, reaching 3 times higher densities than the original ACFs’ apparent densities. The porosity of the monoliths was only slightly decreased with respect to the pristine ACFs, the employed PVDC binder developing additional porosity upon carbonization. The ACF monoliths are essentially microporous and reach BET surface areas of up to 1838 m2 g−1. SEM analysis reveals that the ACFs are well embedded into the monolith structure and that their length was significantly reduced due to the monolith preparation process. The carbonized monoliths were studied as supercapacitor electrodes in two- and three-electrode cells having 2 M H2SO4 as electrolyte. Maximum capacitances of around 200 F g−1 were reached. The results confirm that the capacitance of the bisulfate anions essentially originates from the double layer, while hydronium cations contribute with a mixture of both, double layer capacitance and pseudocapacitance.